A multi-mineral natural product inhibits liver tumor formation in C57BL/6 mice - Aslam, Muhammad N. (2012)
C57BL/6 mice were maintained for up to 18-months on high-fat and low-fat diets with or without a multi-mineral-supplement derived from the skeletal remains of the red marine algae Lithothamnion calcareum. Numerous grossly observable liver masses were visible in animals on the “western-style” high-fat diet sacrificed at 12 and 18 months. The majority of the masses were in male mice (20 out of 100 males versus 3 out of 100 females; p=0.0002). There were more liver masses in animals on the high-fat diet than on the low-fat diet (15 out of 50 on high-fat versus 5 out of 50 on low-fat; p=0.0254). The multi-mineral supplement reduced the number of liver masses in mice on both diets (3 out of 25 male mice in the low-fat diet group without the supplement versus 1 out of 25 mice with supplement; 12 of 25 male mice in the high-fat diet group without the supplement versus 3 of 25 mice with supplement [p=0.0129]). Histological evaluation revealed a total of 17 neoplastic lesions (9 adenomas and 8 hepatocellular carcinomas), and 18 pre-neoplastic lesions. Out of 8 hepatocellular carcinomas, 7 were found in unsupplemented diet groups. Steatosis was widely observed in livers with and without grossly observable masses, but the multi-mineral supplement had no effect on the incidence of steatosis or its severity. Taken together, these findings suggest that a multi-mineral-rich natural product can protect mice against neoplastic and pre-neoplastic proliferative liver lesions that may develop in the face of steatosis.